Design and development of an off-grid e-learning centre for rural communities - Selaule, Vusimuze Edgar (My University, 2015)
The lack of electricity in off-grid rural communities in South Africa (SA) and Africa as well as the budget constraints on these communities restrict these communities from connecting to any online resources (internet and e-books) for educational purposes, thus creating a major contributor to the global digital divide. Renewable energy sources such as solar energy, wind energy and biomass were presented as potential alternatives to grid-connected electricity for remote rural locations. Solar energy was identified as the amply available alternative energy resource in SA. Solar radiation was converted by photovoltaic technology to electricity. National power grid isolation (off-grid) was achieved by using a stand-alone photovoltaic system. Photovoltaic technology classification, material categorisation and system sizing for an e-learning centre was presented. Practical set-ups were utilised to determine the most cost-effective equipment mix of power utilization, power management/storage and ICT equipment to build a pilot e-learning centre. It was established that one photovoltaic panel can be employed to fully recharge a battery of a pilot e-learning centre with an operational period of 7 hours using the available sunlight hours. Owing to the susceptibility of the Vaal Triangle region to thunderstorms causing overcast conditions for days, a ratio of back-up battery capacity (Ah) to number of days (seven hours per day) without sunlight was determined. An algorithm was also derived for sizing the pilot e-learning centre for full scale implementation. Future research recommendations based on this study for a reduced system costs of an off-grid e-learning for rural communities powered by a renewable energy resource were presented. This will increase access to basic education in SA and reduce the global digital divide.
M. Tech. (Electronic Engineering, Faculty of Engineering and Technology), Vaal University of Technology|
Keywords: Off-grid rural communities; Digital divide; Online resources; Renewable energy sources; Solar energy; Photovoltaic system; E-learning centre; Back-up radio capacity; Basic education; 371.334; Solar energy; Internet in education